NGOs and Global Trade: Non-State Voices in EU Trade Policymaking - Diana Potjomkina (Journal of Contemporary European Research, 2018)
Erin Hannah offers a timely and thought-provoking analysis of civil society’s participation in the European Union’s trade policy. Relying on two case studies, the book shows that while the EU has created diverse instruments for engaging with civil society, in practice procedural improvements do not necessarily lead to greater influence for non-governmental organizations (NGOs). Going beyond a purely technical view on NGOs’ access to policy-makers, we should also consider the ideational factors at play.